Revitalisasi Perpustakaan untuk Meningkatkan Minat Baca Anak-Anak Desa Henda - Rafael, Alvin; Pranata, Alsien; Yosepi, Elvida Tri; Chaetrine, Gladies Everlin; Andini, Indri Putri; Tambunan, Junifer Nurselina; Kurniawan, Taufik Andi; Mentari, Theresia (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
Reading interest is very important in this era, because by reading, we can keep the brain functioning well. The purpose of this service is to increase children's reading interest in Henda Village. Library revitalization begins with preparation, implementation, and reporting. The results obtained are an increase in the number of children's visits to the library, which previously had no visits, to an average of 5 visits per day after the library revitalization. It was concluded that library revitalization can increase children's reading interest in Henda Village